Citation Forms in Scientific Texts: Similarities and Differences in L1 and L2 Professional Writing - Okamura, Akiko (Nordic Journal of English Studies, 2008)
This study investigates the use of citation forms in 30 scientific research articles in biology, chemistry and physics written by writers in L1 and L2 contexts. Citation forms were divided into integral (syntactically integrated citation) and non-integral (syntactically non-integrated). Integral citation was further categorized into subject position, non-subject position (passive; clause constituent) and noun phrase (adjunct agent structure; phrase constituent), such as “according to.” Findings show that although few papers were cited in integral citation across the disciplines, writers in the L2 context mainly employed them in a subject position while writers in the L1 context spread them over three positions, creating stylistic variation.